Nghiên cứu tổng quan hệ thống về kế toán quản trị môi trường: Xu hướng, thách thức và định hướng nghiên cứu tương lai - Nguyen Van , Ngoan; Nguyen Phong , Nguyen (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
In the context of climate change and mounting pressure for environmental transparency, Environmental Management Accounting (EMA) has emerged as a strategic tool to support businesses in achieving sustainable development. This study conducts a systematic review of 74 articles from the Scopus database (2000-2025), combining bibliometric analysis with VOSviewer to identify trends, challenges, and research gaps in the EMA field. The findings suggest that EMA is evolving from a technical tool to a strategic management platform, with several prominent research themes. Potential future directions include the integration of digital technologies (e.g., artificial intelligence and blockchain), the development of flexible EMA models for small and medium-sized enterprises (SMEs), the construction of integrated environmental cost indices, and the linkage of EMA with the circular economy, corporate social responsibility (CSR), and green finance. This research contributes to enhancing the theoretical framework and promoting the practical application of EMA, particularly in emerging economies.
Keywords: Environmental performance; Environmental management accounting; Sustainable development